Pengembangan Model Senam DIGIFUN untuk Meningkatkan Partisipasi Gerak Siswa Sekolah Dasar - Karlina Dwijayanti; Arif Rohman Hakim; Fata Laila Fatkhur Rahman (SPRINTER: Jurnal Ilmu Olahraga, 2026)
Physical activity participation among elementary school students in Physical Education, Sports, and Health (PJOK) classes remains low due to the use of conventional and unengaging teaching methods. This study was designed to develop and test the effectiveness of the DIGIFUN Gymnastics model a digital-based learning innovation utilizing a "fun learning" approach to enhance students' physical activity participation. The study employed the Research and Development (R&D) method, carried out through several stages: needs analysis, model design, expert validation, limited-scale trials, product refinement, and effectiveness testing. The research subjects consisted of 30 elementary school students. Data collection techniques included observation, respondent questionnaires, and documentation. Subsequent data processing and analysis involved descriptive quantitative methods, a paired t-test, and an N-Gain test. The results demonstrated a significant increase in students' physical activity participation (t-calculated = 9.87; p < 0.05), with a 30.24% improvement and an N-Gain score of 0.50, placing it in the "medium" category. The DIGIFUN Gymnastics model was deemed valid, practical, and effective as an innovation for PJOK instruction.